KONTRIBUSI TANAMAN ENERGI HUTAN RAKYAT TERHADAP PENDAPATAN RUMAH TANGGA PETANI HUTAN DI SEKITAR PLTU ADIPALA KABUPATEN CILACAP: Contribution of Community Forest Energy Crops to The Income of Forest Farmers' Households Around The Adipala Power Plant in Cilacap Regency (Jurnal ForestrIndo, 2025)
This study aims to analyze the management of energy crops in community forests and their contribution to household income among forest farmers around PLTU Adipala, Cilacap Regency. Using a proportional stratified random sampling method, the study involved 60 respondents from three sub-districts. The results indicate that farmers and their families actively conduct community forest management, starting from land preparation to maintenance using simple tools. Agroforestry systems are applied with alley cropping and enrichment planting patterns, combining timber species (silk tree, teak, mahogany) with non-timber forest products (coconut, Ceylon-olive, clove) and food crops. Marketing is commonly carried out directly from the farmers' land or homes to reduce costs. Income from energy crops contributes 1% to total household income, but with optimized utilization of energy crops and their by-products, such as gamal leaves, this contribution is projected to increase to 25%.hutan rakyat, pendapatan rumah tangga, tanaman energi